MULTIPLE-SHIFT SCHOOLING: INTERNATIONAL CONTEXT AND THE BRAZILIAN CASE - Daros Parente, Claudia da Moto [UNESP] (Univ Federal Sergipe, 2020)
The article systematizes the main concepts, arguments and characteristics of multiple shift schooling in the international context and in Brazil, through bibliographic and documental research. The presentation of the specificities of the multiple-shift schooling in different countries provided elements for the analysis of the Brazilian case. The article highlights the emergence of multiple-shift schooling in the early twentieth century, its widespread nationwide, the emergence of experiences of extended school day, the naturalization of the multiple-shift schooling in the country, the diversity of shifts, school day and schedules and the recent goal of full-time education. Expanding the provision of full-time education does not necessarily mean eliminating multiple-shift schooling. There are still numerous challenges for public schools (half-day or full day). Analysis of school day and full-time education associated with multiple-shift schooling may bring new perspectives to the formulation and implementation of educational policies.
Keywords: Multiple-shift schooling; School day; Full-time education; Educational Policy